2158. Introducing the Population Standardized Infection Ratio (SIR): A Metric that Marries the Device SIR to the Standardized Utilization Ratio (SUR). (26th November 2018) - Fakih, Mohamad; Huang, Ren-Huai; Bufalino, Angelo; Sturm, Lisa; Hendrich, Ann; Haydar, Ziad
Abstract: Background: The device standardized infection ratio (SIR) has been used to compare units' and hospitals' performance for different publicly reported infections. Interventions to reduce unnecessary device use may select a higher risk population that is not accounted for in the current risk adjustments, leading to a paradoxical increase in SIR for facilities that may be high performers. The standardized utilization ratio (SUR) adjusts for device use for different units and facilities. Methods: We calculated the device SIR (calculated based on actual device-days) and population SIR (defined as Σ observed events/ Σ predicted events based on predicted device days) accounting for the facility SUR for both central line-associated bloodstream infections (CLABSI) and catheter-associated urinary tract infections (CAUTI) in 84 hospitals from a single system. The observed and predicted events were compiled at the unit-level and aggregated to facility and system-level SIRs for calendar years 2016 and 2017. Results: The central line SUR was 1.02 for 801, 737 central line-days, with the device SIR of 0.78 and the population SIR of 0.80 (+2.6%, relative increase). On the other hand, the urinary catheter SUR was 0.89 for 758, 966 urinary catheter-days, with the device SIR of 0.87 and the population SIR of 0.77 (−11.5%, relative decrease). The cumulative attributable difference for CAUTI with a SIR of 1 was −107 for the device SIR compared with −185 for the population SIR (73% increase in events prevented). Facilities with a wider variation in SUR tended to have a greater difference in device vs. population SIRs (Figures 1 and 2). Conclusion: Population SIR takes into account device utilization, making it an attractive metric to address overall risk of infection or harm to a patient population, and reduces the risk of selection bias that may impact the device SIR with interventions to reduce device use. Disclosures: All authors: No reported disclosures.